Non-governmental higher educational establish-ments of Russia: modern state, tendencies and perspectives - Vladimir A. Zernov (Высшее образование в России)
The paper of the chairman of the Association of non-governmental higher educational establishments of Russia discusses the modern state of the non-governmental sector of higher education, its structure and the basic indexes. The topical problems of non-governmental HEIs are analyzed, the main ways to solve them are offered, and the perspectives of their development are outlined.